The Influence of TQM on Organizational Commitment, Organizational Citizenship Behaviours, and Individual Performance - Vera CARLOS; Luis MENDES; Luis LOURENÇO (Transylvanian Review of Administrative Sciences, 2014)
The main aim of this research is to analyze if the adoption of Total Quality Management (TQM) principles is really associated with more favor-able attitudes from collaborators in organiza-tions, specifcally in Higher Education. Empirical data were collected through a questionnaire ap-plied to 82 faculty members at higher education institutions (HEIs). Although the relationship of dependence between TQM and individual perfor-mance was not confrmed, the results obtained do corroborate the idea, according to which the adoption of TQM principles is associated with more favorable attitudes regarding organization-al commitment and organizational citizenship behaviors. Materializing specifc work-related at-titudes cannot be directly imposed or prescribed. The fndings highlight the importance of enhanc-ing its antecedents, and suggest TQM as a po-tential signifcant opportunity to leverage such behaviors most benefcially. This is one of the few studies that focus on the infuence of TQM concerns in work-related attitudes and behaviors in the specifc context of HEIs.